Marine Reservoir Age Variability Over the Last Deglaciation: Implications for Marine CarbonCycling and Prospects for Regional Radiocarbon Calibrations. Issue 11 (29th November 2019) - Skinner, L. C.; Muschitiello, F.; Scrivner, A. E.
Abstract: Marine radiocarbon dates, corrected for ocean‐atmosphere reservoir age offsets (R‐ages), are widely used to constrain marine chronologies. R‐ages also represent the surface boundary condition that links the ocean interior radiocarbon distribution (i.e., "radiocarbon ventilation ages") to the ocean's large‐scale overturning circulation. Understanding how R‐ages have varied over time is therefore essential both for accurate dating and for investigations into past ocean circulation/carbon cycle interactions. A number or recent studies have shed light on surface reservoir age changes over the last deglaciation; however, a clear picture of global/regional spatiotemporal patterns of variability has yet to emerge. Here we combine new and existing reservoir age estimates to show coherent but distinct regional reservoir age trends in the subpolar North Atlantic and Southern Ocean. It can be further shown that similar but lower amplitude changes occurred at midlatitudes in each hemisphere. An apparent link between regional patterns of reservoir age variability and the "thermal bipolar seesaw" suggests a causal link with changes in ocean circulation, mixed‐layer depth, and/or sea ice dynamics. A further link to atmospheric CO2 is also apparent and underlines a potentially dominant role for changes in the ocean's "disequilibrium carbon" pool, rather than changes in ocean transport, in deglacial CO2 change. The existence of significant R‐age variability over the last deglaciation poses a problem for marine radiocarbon age calibrations. However, its apparent regional consistency also raises the prospect of developing region‐specific marine calibration curves for radiocarbon‐dating purposes. Plain Language Summary: Radiocarbon is widely used to date ancient fossil material, including marine shells, reaching back to ~40, 000 years. Less well known, is its use as a marine carbon cycle tracer. Both of these applications require knowledge of how the surface ocean's radiocarbon activity has changed over time, which presents a serious challenge. In this study, we demonstrate that the polar regions of the Atlantic Ocean have experienced significant changes in their radiocarbon activity. These are linked to both regional climate change and atmospheric CO2 fluctuations, and thus serve to emphasize the important role of processes acting at the sea surface, including sea ice variability in particular, in controlling the heat and carbon storage in the ocean. At the same time, by demonstrating regional consistency of marine radiocarbon trends, our results open up the possibility of improved radiocarbon dating of marine material in future. Key Points: Significant, regionally consistent 14 C reservoir age changes occurred at middle and high latitudes across the last deglaciation Northern and southern R‐age patterns differ, underlining the role of ocean circulation and/or sea ice linked to the "bipolar seesaw" Regional marine calibration curves are proposed as a viable means of improving marine radiocarbon calibration beyond the Holocene